2021
DOI: 10.1177/16878140211020878
|View full text |Cite
|
Sign up to set email alerts
|

Design and thermal characteristic analysis of motorized spindle cooling system

Abstract: The thermal deformation of high-speed motorized spindle will affect its reliability, so fully considering its thermal characteristics is the premise of optimal design. In order to study the thermal characteristics of high-speed motorized spindles, a coupled model of thermal-flow-structure was established. Through experiment and simulation, the thermal characteristics of spiral cooling motorized spindle are studied, and the U-shaped cooled motorized spindle is designed and optimized. The simulation results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Spindle temperature gradually tended to stable as cooling water flow increases [31]. Zhang et al [32] investigated the effect of water runner diameter and flow rate on spindle cooling during the cooling process. In a certain area, larger flow channel diameter and flow rate can reduce the temperature and radial heat elongation effectively.…”
Section: Coolant Flow Statusmentioning
confidence: 99%
“…Spindle temperature gradually tended to stable as cooling water flow increases [31]. Zhang et al [32] investigated the effect of water runner diameter and flow rate on spindle cooling during the cooling process. In a certain area, larger flow channel diameter and flow rate can reduce the temperature and radial heat elongation effectively.…”
Section: Coolant Flow Statusmentioning
confidence: 99%
“…Zhang et al studied a coupled model of thermal-flow-structure. The simulation results showed that when the diameter of the cooling chan-nel is 7 mm, a spiral cooling system develops a lower temperature but greater radial thermal deformation than a U-shaped cooling system [4]. Su et al established a thermal fluid-solid coupling model of a hydrostatic spindle system using the finite volume method.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al 10 combined heat transfer and nonlinear dynamics, a new theoretical method was proposed to study the thermal behavior of inter-shaft bearing considering the nonlinear dynamic characteristics of double-rotor system. The thermal-flow-structure coupling analysis model was established by Zhang et al 11 to analyze the thermal characteristics of motorized spindle, which provided a good basis for the optimization design of thermal characteristics of motorized spindle. Zhao et al 12 proposed a measurement method of temperature distribution in inner and outer rings of bearing, and a calculation method to study the temperature distribution of bearing and its distribution.…”
Section: Introductionmentioning
confidence: 99%